Engineering geology of Waterside Green, Sydney, Australia (Journal of Nepal Geological Society, 2006)
Development of low-lying land affected by high water table in saline and sodic soils and local swampy areas remains a challenge for the local government, developers, and other regulators. The development control plan for a proposed residential or commercial subdivision in such a site in Penrith, Sydney, Australia, states that the drainage and stormwater management systems within and across the site should be improved and proposed buildings should be constructed on the ground higher than the 100-year flood level. This paper presents the results of engineering geological and geotechnical investigations for the proposed subdivision. The subsurface profile at the site comprises alluvial deposits underlain by residual soil, which in turn is underlain by shale and sandstone. In the eastern portion of the site, the alluvial deposits comprise a sequence of clay, sand and gravel, and in the western portion they contain a succession of clean sand and gravel. The alluvium in the eastern portion of the site is saline whereas it is generally non-saline in the western portion. All saline soils are sodic and most non saline ones are non-sodic. This paper discusses the suitability of on-site soils for use in a structural fill and impermeable clay liner as well as the management of saline and dispersive soils.